Design of Charger Controller on Wind Energy Power Plant with Arduino Uno Based on Pi Controller - Nugraha, Anggara Trisna; Pambudi, Dwi Sasmita Aji; Utomo, Agung Prasetyo; Priyambodo, Dadang (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2021)
Technological developments are increasing every day. Most human activities do not escape the use of electrical energy. The increase in world fuel oil and its scarcity has led to many new innovations, one of which is the use of renewable energy. The most widely used renewable energy is solar, wind, and hydro energy. In order to support the effectiveness of the generator, a charger controller is needed to maintain battery performance. In this accumulator, the maximum voltage required to charge is 14.4 Volts. The problem that arises is how the voltage generated from the generator does not match the voltage required in the battery charging process. From this problem, a charger controller with a buck converter circuit with the PI method was made to stabilize the output voltage for charging. The aim o this study is to make a battery charger that can stabilize the level voltage of the battery charger. From the research, it was found that the efficiency value of the charger controller is 83-95%, and the average error percentage is 1.373%. For this reason, it can be concluded that the charge controller has good performance in terms of efficiency and percentage of output voltage error. The charger controller is expected to maintain battery performance and the lifetime of the battery